A nonlocal SIR epidemic problem with double free boundaries. (November 2022) - Chen, Yujuan; Wang, Mingxin
Abstract: This paper is concerned with a new nonlocal SIR epidemic model with double free boundaries. Our results show that the disease will spread if the basic reproduction number R 0 ( a − r b, ( − h 0, h 0 ) ) ≥ 1 ; whereas, when the basic reproduction number R 0 ( a − r b, ( − h 0, h 0 ) ) < 1, the disease will spread or not depending on the expanding ability μ of infected population.